A Normal Range of KL-6/MUC1 Independent of Elevated SP-D Indicates a Better Prognosis in the Patients with Honeycombing on High-Resolution Computed Tomography - Hisata, Shu; Kimura, Yuichiro; Shibata, Naoko; Ono, Shuichi; Kobayashi, Takao; Chiba, Shigeki; Ohta, Hiromitsu; Nukiwa, Toshihiro; Ebina, Masahito (Pulmonary Medicine, 2011)
Both SP-D and KL-6/MUC1 are established biomarkers of the interstitial pneumonias, including idiopathic pulmonary fibrosis (IPF), but the causes and clinical outcomes based on their independent effects are not known. Eleven asymptomatic patients, detected with honeycombing on high-resolution computed tomography (HRCT), were compared with 17 other IPF outpatients having slight respiratory symptoms and honeycombing as well. Although SP-D was increased in both groups, KL-6 was significantly higher in the symptomatic IPF group. When the patients (n=11) having both biomarkers elevated were compared with the other patients (n=6) with only SP-D elevated, the distribution of fibrotic lesions with honeycombing on HRCT was larger and the survival time was shorter in the patients having both biomarkers elevated. Immunohistochemical analysis also differentiated these biomarkers in the lung. These results suggest both a cause and the prognostic value of dissociation of these biomarkers.